2017
DOI: 10.5424/sjar/2017151-10266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mycobacterium avium subsp. paratuberculosis serostatus on carcass weight and conformation and fat cover scores

Abstract: The paper was designed to assess the influence of Mycobacterium avium subsp. paratuberculosis (MAP) infection status of cows at culling (antibody positive vs negative) on carcass traits: weight and conformation and fat cover scores. A generalized least squares linear model was used to assess the influence of MAP on weight. Subsequently, a random effects logistic regression was completed in order to model the relation between MAP and conformation score (fair vs poor carcasses). A random effects ordered logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A possible association between PTB and meat quantity and quality was investigated in several studies. A reduction in carcass weight of −39.78 kg or −12.4% ( p = < 0.0001) ( 70 ) and −58.45 kg ( p = < 0.001) ( 80 ) for serum ELISA positive cows was reported. The slaughter weight for serum ELISA positive cows was reduced by up to −10% and up to −15% if they were also fecal culture positive, resulting in a reduction of slaughter value of −17% and −31%, respectively ( 81 ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…A possible association between PTB and meat quantity and quality was investigated in several studies. A reduction in carcass weight of −39.78 kg or −12.4% ( p = < 0.0001) ( 70 ) and −58.45 kg ( p = < 0.001) ( 80 ) for serum ELISA positive cows was reported. The slaughter weight for serum ELISA positive cows was reduced by up to −10% and up to −15% if they were also fecal culture positive, resulting in a reduction of slaughter value of −17% and −31%, respectively ( 81 ).…”
Section: Resultsmentioning
confidence: 92%
“…In another study, losses were estimated at US$ 296/per clinical case ( 49 ). Mato et al ( 80 ) found that seropositive cows were more likely to have poor carcass quality. They were 3.85 times more likely to have a poor carcass conformation score instead of fair and they had significantly lower fat cover scores.…”
Section: Resultsmentioning
confidence: 99%
“…This disease causes serious economic losses in dairy farming, mainly as a result of reduced milk yield [ 3 , 4 ], increased susceptibility to other diseases, particularly mammary infections [ 5 ], loss of bodyweight [ 6 ] and consequential premature culling [ 7 ]. Paratuberculosis has also been related to reduced fertility rates [ 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…milk yield (Richardson and More, 2009), increased susceptibility to other diseases, especially mammary infections (Tiwari et al, 2005), loss of body weight (Mato et al, 2017), and consequential premature culling (Mato et al, 2015). Paratuberculosis has also been related to reduced fertility rates (Smith et al, 2010).…”
mentioning
confidence: 99%